Sex Education and Gender in Mexican Elementary Schools: What Do Textbooks and Teachers Have to Say? - Rosales-Mendoza, Adriana Leona (2017)
The aim of this research was to review and analyze, from a gender perspective, the sexuality and gender contents included in the textbooks of Natural Sciences, Civics, and Ethics for the fourth, fifth and sixth grade of elementary school; this was done to point out the strengths and weaknesses on how to address these issues. We, likewise, inquired about teacher training in sexuality and gender topics, for which we relied on the testimony of four interviews with primary school teachers from Quintana Roo and Yucatán (two states of the Mexican southeast): two of them were from fifth grade, and two others were from sixth grade. The results showed that the contents of the textbooks reduce the sexuality topic to reproduction, and they do not include eroticism, which is considered relevant in the approach to comprehensive sexuality education. Similarly, these contents transmit heteronormative ideas regarding emotional bonds, and do not fully incorporate the gender perspective, since they fail to denounce the inequality between men and women. Teacher training is deficient and it emphasizes the effect of the hidden curriculum, as stereotypes and prejudices of gender and sexuality are being transmitted.